2012
DOI: 10.1016/j.bpj.2012.07.016
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Model for Type I and II IP3R Accounting for Mode Changes

Abstract: Based upon an extensive single-channel data set, a Markov model for types I and II inositol trisphosphate receptors (IP(3)R) is developed. The model aims to represent accurately the kinetics of both receptor types of IP(3)R depending on the concentrations of inositol trisphosphate (IP(3)), adenosine trisphosphate (ATP), and intracellular calcium (Ca(2+)). In particular, the model takes into account that for some combinations of ligands the IP(3)R switches between extended periods of inactivity alternating with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(128 citation statements)
references
References 21 publications
4
123
0
1
Order By: Relevance
“…The probability distribution P(p, j, J | Y) approximated by the RJMCMC sampler answers several questions at once. Most of these questions cannot be answered confidently or cannot be answered at all by the heuristic algorithm described by Ionescu et al [45] or approaches based upon moving averages like in Siekmann et al [52]. Interestingly, for 1000 nM Ca 2+ , type I IP 3 R shows some evidence for a third mode at probabilities between 20 and 30% which has also been observed by Ionescu et al [45], who reported a mode of intermediate activity for their type I IP 3 R dataset (figure 1a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The probability distribution P(p, j, J | Y) approximated by the RJMCMC sampler answers several questions at once. Most of these questions cannot be answered confidently or cannot be answered at all by the heuristic algorithm described by Ionescu et al [45] or approaches based upon moving averages like in Siekmann et al [52]. Interestingly, for 1000 nM Ca 2+ , type I IP 3 R shows some evidence for a third mode at probabilities between 20 and 30% which has also been observed by Ionescu et al [45], who reported a mode of intermediate activity for their type I IP 3 R dataset (figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, changes of ligand concentrations have little influence on the modulation of the short-term kinetics of openings and closings. This idea has been realized in a model by Siekmann et al [52], who represented modal gating of the IP 3 R by two ligand-independent models that were connected by ligand-dependent transition rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither is ours the first instance where a model representing the modal behavior of InsP 3 R is used for simulating puffs. Siekmann et al developed a six-state model incorporating the modal behavior of the channel [33] that was shown to reproduce the statistics of puffs [34] and whole-cell oscillations [35]. Simplifying the six states to a two-state model by getting rid of the intra-modal structure and using the two versions of the model, Siekmann et al [36] demonstrated that the fundamental process governing the generation of Ca 2+ puffs and oscillations is primarily controlled by the inter-modal structure, not the intra-modal structure.…”
Section: Discussionmentioning
confidence: 99%
“…See Appendix A for details of the boundary flux and reaction terms depicting calcium transporters and buffering. Briefly, we deploy a model of the MCU based on observations (40), include the LetM1 as characterized (37), and utilize a recent IP 3R model (64 Table 2 for a model geometry region and corresponding biological domain summary; each boundary flux term is also given in Table 3.…”
Section: Model Equationsmentioning
confidence: 99%